Quality of Soil Loosening by Subsoilers of a Combined Machine (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The purpose of the study is to study the influence of subsoiler parameters on the quality of soil loosening when preparing the soil for sowing melons under a film using a combined machine. The authors have developed a combined machine for preparing the soil for sowing melons and melons under film. A design diagram of the developed combined machine is presented. The completeness of soil loosening by machine subsoilers is theoretically determined based on their parameters and relative position.The basic principles and methods of classical mechanics, mathematical analysis and statistics were used in this study.Theoretical and experimental studies have established that the pairwise arrangement of subsoilers of a combined machine inclined to the right and left with working surfaces facing each other, as well as offset relative to each other in the longitudinal plane, provides the required quality of work. With a longitudinal distance between subsoilers of 75 cm and a transverse distance of 60 cm, high-quality loosening of the soil is ensured according to the requirements.